Analysis of Porosity Effects on Unsteady Stretching Permeable Sheet - SINGH, Phool; KUMAR, Anoop; TOMER, Nagender Singh; SINHA, Deepa (Walailak Journal of Science and Technology (WJST), 2013)
The aim of this paper is to analyze two-dimensional unsteady flow of a viscous incompressible fluid about a stagnation point on a permeable stretching sheet in presence of a time dependent free stream velocity. Fluid is considered in the porous media with radiation effect. The Rosseland approximation is used to model the radiative heat transfer. Using a time-dependent stream function, partial differential equations corresponding to the momentum and energy equations are converted into non-linear ordinary differential equations. The numerical solutions of these equations are obtained by using the Runge-Kutta Fehlberg method with the help of shooting technique. In the present work, the effect of porosity parameter, radiation parameter and suction parameter on flow and heat transfer characteristics are discussed. The skin-friction coefficient and the Nusselt number at the sheet are computed and discussed. The results reported in the paper are in good agreement with published work in literature by other researchers. doi:10.14456/WJST.2014.13